Exosomal microRNAs: implications in the pathogenesis and clinical applications of subarachnoid hemorrhage - Liao, Lishang; Wang, Haoran; Wei, Deli; Yi, Mingliang; Gu, Yingjiang; Zhang, Mingwei; Wang, Li (Frontiers in Molecular Neuroscience, 2023)
Subarachnoid hemorrhage (SAH) is a severe acute neurological disorder with a high fatality rate. Early brain injury (EBI) and cerebral vasospasm are two critical complications of SAH that significantly contribute to poor prognosis. Currently, surgical intervention and interventional therapy are the main treatment options for SAH, but their effectiveness is limited. Exosomes, which are a type of extracellular vesicles, play a crucial role in intercellular communication and have been extensively studied in the past decade due to their potential influence on disease progression, diagnosis, and treatment. As one of the most important components of exosomes, miRNA plays both direct and indirect roles in affecting disease progression. Previous research has found that exosomal miRNA is involved in the development of various diseases, such as tumors, chronic hepatitis, atherosclerosis, diabetes, and SAH. This review focuses on exploring the impact of exosomal miRNA on SAH, including its influence on neuronal apoptosis, inflammatory response, and immune activation following SAH. Furthermore, this review highlights the potential clinical applications of exosomal miRNA in the treatment of SAH. Although current research on this topic is limited and the clinical application of exosomal miRNA has inherent limitations, we aim to provide a concise summary of existing research progress and offer new insights for future research directions and trends in this field.